Resilience in torture survivors: reflections, learnings and ways forward - Pérez-Sales, Pau (Torture Journal, 2023)
The paper develops initial reflections on the possibility of resilience in torture survivors and how resilience would be defined in that case, who would be resilient and whether it is possible to learn to be resilient. The second part suggests a comprehensive list of individual and collective resilience mechanisms relevant during and after the experience of torture.